Do Differences in Peak Oxygen Uptake in Men and Women Explain Recovery from Intermittent Exercise? 能以男女最大攝氧量的不同解釋其最大強度重複運動的恢復過程嗎？ - CHIA, Michael (Asian Journal of Physical Education & Recreation, 2003)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The purpose of the study was to examine if differences in peak oxygen uptake between men and women explain their recovery from maximal effort intermittent exercise. 24 men (25.3±2.7yrs; 1.75±0.06m; 69.3±8.9kg) and 24 women (23.2±2.2yrs; 1.63±0.06m; 53.5±7.6kg) participated in the study. On separate occasions, participants completed a peak oxygen uptake (peak V02) treadmill test and five 20s cycle sprints, which were separated by a 45s recovery interval. Peak V02, PP and MP in the repeated sprints and blood lactate measurements were taken. Results showed that men had higher peak V02 than women (53.2±8.7 vs. 42.8±6.8 ml/kg BM/min, p<0.05), but there was no sex difference recovery of Wingate Anaerobic Test power between successive sprints when PP and MP in the sprints were expressed as a percentage of the highest attained in the first sprint (64-88% in men versus 67-90% in women). Differences in peak V02 between men and women did not explain the recovery of men and women during intermittent maximal exercise. 本文的目的是研究能否以男女之間最大攝氧量的不同來解釋其最大強度重複運動的恢復過程。24名男性(年齡為25.3 ± 2.7歲；身高為1.75 ± 0.06米；體重為69.3 ± 0.9公斤)及24名女性(年齡為23.2 ± 2.2歲；身高為1.63 ±.06米；體重為53.5 ± 7.6公斤)在跑台上進行逐級遞增負荷的運動以測定其最大攝氧量(peak V02)，並選擇不同的日期，在自行車功率儀上完成5次最快速度的踏車運動，各次運動之間以45秒的恢復時間為間隔，以測定受試者每次運動的最髙功率和平均功率，並計算出其它各次運動的最高功率和平均功率占首次運動最高功率和平均功率的百分比率。實驗結果顯示男性的最大攝氧量明顯高于女性，分別為53.2 ± 8.7毫升/公斤體重/分與42.8 ± 6.8毫升/公斤體重/分(p<0.05)，但男女之間各次快速踏車運動的最高功率和平均功率的百分比無明顯差異，男性為64-88%，而女性為67-90%。本結果表明最大攝氧量的不同並不足以解釋男女之間最大強度重複運動的恢復過程。